Textile Industry CSR Disclosure Trends : Reflections from India and Malaysia - Govindasamy, Vimala; Suresh, Kalyani; Gunasekar, Sangeetha (Prabandhan: Indian Journal of Management, 2018)
This paper examined the Corporate Social Responsibility Disclosures of South Indian and Malaysian textile firms to understand the levels of transparency in terms of a comparison between the companies’ strategic implementation of CSR vs their efforts towards public perception of their CSR efforts. Paired t - test and binary regression were used to measure CSR Disclosure Indexes within the textile firms, culled from their corporate website communications and annual reports. It was found that CSR disclosure practices varied significantly across strategic implementation and perceived CSR practices for both the countries, with higher levels of perceived CSR. Presently, textile firms in both countries do not seem to provide an accurate image of CSR actions and initiatives. The study is a valuable contribution to academic literature as well as textile firms and stakeholders in making the heterogeneous strategic - perceived CSR link more relevant and transparent, and thus, furthering knowledge on the relationship between CSR reporting and implementation. The study also filled the gap in academic literature in terms of highlighting a model of CSR disclosures that would enable aÂ cross - country study of the dynamics of firms’ CSR approach in terms of transparency and value - enhancement of CSR activities.